SISTEM PAKAR UNTUK MENDIAGNOSA KANKER LEHER RAHIM DENGAN METODE FORWARD CHAINING - Candra, Bintang Bayu Abie; Yupianti, Yupianti; Sapri, Sapri (UNIVED Press, 2024)
Dr. Hospital M. Yunus Bengkulu City is one of the hospitals located in Bengkulu City. At Dr. Hospital. M. Yunus, Bengkulu City does not yet have a computer system or computer application that can be used, and also in this hospital patients still have to come to the hospital to consult a doctor or nurse directly, so when there is no specialist doctor or nurse the patient is very difficult To consult, it is less effective to consult directly with a doctor or nurse, so an application is needed to help patients deal with cervical cancer, because with this application, it also helps patients to know what their disease is and what the solution is. Based on the results of the discussion and testing that has been carried out, it can be concluded that this expert system for diagnosing cervical cancer can help with early diagnosis of cervical cancer by including the symptoms experienced by the patient using the Forward Chaining Method approach. Based on patient testing which was carried out by selecting symptom codes G1, G2, G3 and G4, the diagnosis results were obtained using forward chaining, namely cervicitis with a percentage of 100%, cervical cancer with a percentage of 37.5% and portio erosion with a percentage of 25%. Based on the test results The black box that has been carried out, the functionality of the expert system for diagnosing cervical cancer using the Forward Chaining Method can now be implemented and can provide information on consultation results and determine an early diagnosis of cervical cancer.